The sign revolution: the existential becoming of simulation - Luca Cardone (Lexicon Philosophicum)
This essay aims to investigate the status of simulacra and simulation within the specific aesthetic-perceptual context, emphasizing the emergence of representations obtained through technical apparatuses. By discussing and elaborating on a key aspect of the philosophy of media theorist Vilém Flusser, the intent of these reflections is to observe that, on the one hand, technical images arise as the processing and resolution of an existential problem related to world representations that emerged during the seventeenth and eighteenth centuries through a physico-mathematical revolution. On the other hand, this resolution has manifested the most impactful properties of simulacra and simulation; issues that a philosophy of sensation is capable of bringing into focus and problematizing.